1988
DOI: 10.2165/00003495-198836050-00004
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Metipranolol

Abstract: Metipranolol is a non-selective beta-adrenoceptor blocking agent used for the topical treatment of elevated intraocular pressure in patients with chronic open angle glaucoma or ocular hypertension. In double-blind comparative studies of up to 4 months duration, metipranolol 0.1 to 0.6% produced comparable reductions in intraocular pressure to timolol 0.25 to 0.5% and levobunolol 0.5%, lowering pressure by about 20 to 29% from baseline. Metipranolol has been well tolerated by most patients, producing only minor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…In this study, mean IOP decreases ranging from 31 to 38% from baseline were observed with the reductive effects of the dose persisting for up to 24 h and longer [ 209 ]. Metipranolol 0.1–0.6% demonstrated IOP reduction effects ranging from 20 to 29% decreases from baseline, determined to be comparable to the therapeutic activity of timolol 0.25–0.5% and levobunolol 0.5% [ 210 , 211 ]. In vivo studies regarding the unintended ocular effects of metipranolol have reported consequential corneal alterations: reduced number of microvilli covering the outer plasma membrane and widened intracellular spaces on the surface cell layers.…”
Section: Glaucoma Therapeuticsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, mean IOP decreases ranging from 31 to 38% from baseline were observed with the reductive effects of the dose persisting for up to 24 h and longer [ 209 ]. Metipranolol 0.1–0.6% demonstrated IOP reduction effects ranging from 20 to 29% decreases from baseline, determined to be comparable to the therapeutic activity of timolol 0.25–0.5% and levobunolol 0.5% [ 210 , 211 ]. In vivo studies regarding the unintended ocular effects of metipranolol have reported consequential corneal alterations: reduced number of microvilli covering the outer plasma membrane and widened intracellular spaces on the surface cell layers.…”
Section: Glaucoma Therapeuticsmentioning
confidence: 99%
“…In vivo studies regarding the unintended ocular effects of metipranolol have reported consequential corneal alterations: reduced number of microvilli covering the outer plasma membrane and widened intracellular spaces on the surface cell layers. These observations, however, were deemed to be insignificant considering the overall well-being of the eye [ 211 ]. At the clinical level, research endeavors monitored the hemodynamic effects of the ocular instillation of the drug, demonstrating that systolic or diastolic blood pressure and heart rate are not significantly altered following ocularly instilled metipranolol 0.1 to 0.6% [ 212 ].…”
Section: Glaucoma Therapeuticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Levobunolol undergoes enzymatic hydrolysis to generate dihydrolevobunolol, a potent β-adrenoceptor blocker in the cornea, aqueous humor and iris-ciliary body. Both these molecules exhibit comparable activity in reducing IOP [18, 19]. Carteolol, a hydrophilic non-selective partial β-adrenoceptor antagonist reduces IOP and is more preferable in patients with bradycardia, heart failure and pulmonary complications.…”
Section: Glaucomamentioning
confidence: 99%